SCHIZOPHRENIA INFORMAL CAREGIVERS OPTIMISM: THE EFFECTIVENESS OF QURAN RECITATION LISTENING THERAPY - Fuad Nashori; Ratna Azkia Rakhmandari; Abdi Winarni Wahid; Ratna Yunita Setiyani; Muwaga Musa; Ardhito Faza Akhnaf (Universitas Islam Indonesia, 2022)
Informal caregivers are usually uncertain about the recovery and life expectancy improvement of schizophrenic patients. This study aimed to determine Quran recitation listening therapy's effectiveness in increasing optimism in schizophrenia informal caregivers. Optimism was measured using the Life Orientation Test-Revision (LOT-R) developed by Scheier, Carver, and Bridges. Quran recitation listening therapy was conducted using the tartil method. The Qori’ recited surah Ar-Rahman with and without interpretation for experimental groups 1 and 2 comprising informal caregivers. Furthermore, hypotheses were tested quantitatively with the Wilcoxon analysis technique to determine the effect of the Quran recitation listening therapy on optimism. The results showed that Quran recitation listening therapy with and without interpretation effectively increased informal caregivers' optimism. The finding justified the theory that Islamic religious intervention in the Quran recitation listening therapy with and without interpretation effectively increases optimism